Mechanism of intestinal injury induced by WNT2B high-expressed fibroblasts in Crohn's disease - Cheng, Y L (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2023)
Objective: To explore the mechanism of intestinal tissue damage induced by macrophages activated by WNT2B high-expressed fibroblasts. Methods: This study involved biological information analysis, pathological tissue research and cell experimental research. The biological information of the colon tissue from the children with inflammatory bowel disease in previous study was analyzed again with single-cell sequencing. The pathological tissues were collected by colonoscopy from 10 children with Crohn's disease treated in the Department of Gastroenterology of Guangzhou Women and Children's Medical Center from July 2022 to September 2022. According to the findings of colonoscopy, tissues with obvious inflammation or ulceration were classified as the inflammatory group, while tissues with slight inflammation and no ulceration were classified as the non-inflammatory group. HE staining was performed to observe the pathological changes of the colon tissues. Macrophage infiltration and CXCL12 expression were detected by immunofluorescence. In terms of cell experiments, fibroblasts transfected with WNT2B plasmid or empty plasmid were co-cultured with salinomycin treated or non-treated macrophages, respectively; the expression of proteins through Wnt classical pathway were detected by western blotting. Macrophages treated with SKL2001 were used as the experimental group, and those with phosphate buffer as the control group. The expression and secretion of CXCL12 in macrophages were detected by quantitative Real-time PCR and enzyme-linked immunosorbent assay (ELISA). T-test or rank sum test were used for the comparison between groups. Results: Single-cell sequencing analysis suggested that macrophages were the main cells in inflammatory bowel disease colon tissue, and there was interaction between WNT2B high-expressed fibroblasts and macrophages. HE staining of the 10 patients ((9.3±3.8) years old, 7 males and 3 females) showed that the pathological score of colon tissue in the inflammatory group was higher than that in the non-inflammatory group (4 (3, 4) vs. 2 (1, 2) points, Z=3.05, P=0.002). Tissue immunofluorescence indicated that the number of infiltrating macrophages in the inflammatory group was significantly higher than that in the non-inflammatory group under high power field of view (72.8±10.4 vs.8.4±3.5, t=25.10, P<0.001), as well as the number of cells expressing CXCL12 (14.0±3.5 vs. 4.7±1.9, t=14.68, P<0.001). In cell experiments, western blotting suggested an elevated level of glycogen synthase kinase-3β phosphorylation in macrophages co-cultured with fibroblast transfected with WNT2B plasmid, and salinmycin could reverse this change. Real-time PCR suggested that the transcription level of CXCL12 in the experimental group was higher than that in the control group (6.42±0.04 vs. 1.00±0.03, t=183.00, P<0.001), as well as the expression and secretion of CXCL12 by ELISA ((465±34) vs. (77±9) ng/L, t=13.21, P=0.006). Conclusion: WNT2B high-expressed fibroblasts can secrete WNT2B protein and activate the Wnt classical signaling pathway thus enhancing the expression and secretion of CXCL12 in macrophages, inducing the development of intestinal inflammation of Crohn's disease